Paradigma Moderasi Beragama: Revitalisasi Fungsi Pendidikan Islam dalam Konteks Multikultural Perspektif Pemikiran Imam al-Ghazali - Nasri, Ulyan; Tabibuddin, M. (Jurnal Ilmiah Profesi Pendidikan, 2023)
This research aims to explore the thoughts of Imam al-Ghazali as the foundation of the religious moderation paradigm in Islamic education and examine its relevance in the context of a multicultural society. Imam al-Ghazali is one of the prominent Islamic scholars who advocated views that support religious moderation, tolerance, and interfaith harmony. This study employs the library research method to analyze and summarize Imam al-Ghazali's thoughts and understand how these views can be applied in the context of multicultural Islamic education. The research findings demonstrate that Imam al-Ghazali's thoughts reflect a strong paradigm of religious moderation. He emphasized the importance of a balanced understanding of religion, as well as values such as tolerance, compassion, and peace in Islam. These concepts have significant relevance in the context of a multicultural society, where religious and cultural differences are an unavoidable reality. Islamic education based on Imam al-Ghazali's thoughts can play a crucial role in promoting better interfaith understanding, reducing conflicts, and building harmonious relationships in a multicultural society. Therefore, this research underscores the importance of revitalizing the paradigm of religious moderation in Islamic education and integrating it into the Islamic education curriculum. The implications of this research highlight the need for genuine efforts in developing Islamic education that focuses on the values of religious moderation as a path towards a more inclusive, tolerant, and peaceful society in the era of multiculturalism.